ANALISIS TINGKAT PENGETAHUAN PETANI KOPI TERHADAP PENANGANAN KOPI PASCA PANEN MENGGUNAKAN TEKNIK ANAEROB - Nirmawati, Nirmawati; Rengganis, Baiq Santi (AGRIBIOS, 2025)
Knowledge level of farmers in post-harvest coffee handling in Sajang Village, Sembalun District, East Lombok Regency. This study aims to determine the level of knowledge of farmers in handling post-harvest coffee using anaerobic techniques in Sajang Village, Sembalun District, East Lombok Regency. Sampling in this study was done by taking all the population into respondents, namely farmers who are members of the Bumbi tani lestari Indonesia farmer group in Sajang Village, Sembalun District, East Lombok Regency as many as 40 people. Data analysis used in this research is quantitative descriptive data analysis. The results showed that the level of knowledge of farmers in handling post-harvest coffee using anaerobic techniques which include sorting is known to be high with a value of 3 with a percentage of 57%, fermentation is known to be medium with a value of 2 with a percentage of 50%, drying is known to be high with a value of 3 with a percentage of 55%, storage and skin grinding is known to be medium with a value of 2 with a percentage of 63%.